Node.js: Using JavaScript to Build High-Performance Network Programs - Tilkov, Stefan; Vinoski, Steve (IEEE internet computing, 2010)
One of the more interesting developments recently gaining popularity in the server-side JavaScript space is Node.js. It's a framework for developing high-performance, concurrent programs that don't rely on the mainstream multithreading approach but use asynchronous I/O with an event-driven programming model.